Analysis of Small Micro Business Sector on the Welfare of Small Micro Enterprises in North Sumatra - Diwayana Putri Nasution; Syaad Afifuddin; Irsad Irsad; Rahmanta Rahmanta (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
Micro and small enterprises (UMK) are businesses that absorb the most labor in Indonesia. The purpose of this study is to look at the effect of the MSE sector (UMK investment variable, UMK digitization variable, and UMK entrepreneurship variable) on the variable for the employment of MSEs and the variable for MSE actors. The analytical method used is the simultaneous analysis method using panel data sourced from BPS North Sumatra Province. The results of the first equation study of the MSE investment variable have a significant positive effect on the absorption of MSEs in North Sumatra. The results of the second study indicate that the digitization of MSEs has a positive and insignificant effect on the welfare of MSEs in North Sumatra. The MSE entrepreneurship variable has no significant positive effect on the welfare of MSE actors in North Sumatra. The variable of employment of MSEs has a significant positive effect on the welfare of MSEs in North Sumatra. The results show that Pappas and Mark Hirshey's theory applies, namely the demand for MSEs in North Sumatra is proven to be a derivative labor demand because it is based on the development of micro and small businesses in North Sumatra.